PEMENUHAN HAK WARIS PEREMPUAN DALAM BUDAYA PATRIARKI PADA SUKU BATAK TOBA DI DESA UNTEMUNGKUR KECAMATAN MUARA - Naomi Christin; Emilda Firdaus; Ulfia Hasanah (Media Keadilan: Jurnal Ilmu Hukum, 2023)
This research is related to the Fulfillment of Women's Inheritance Rights in the Patriarchal Culture of the Toba Batak Tribe in Untemungkur Village. Fulfillment of women's inheritance rights in fact has not been appropriately fulfilled. This happens because of the patriarchal culture that is still ingrained in people's lives, especially the Toba Batak whose heirs are men and not women. The research method used is a type of sociological legal research. The research location was carried out in Unte Mungkur Village, Muara District, North Tapanuli Regency. The data sources used are primary data and secondary data. Data collection techniques in this study were questionnaires, interviews, literature review, and ended with a deductive thinking method. The first result of this study is that the fulfillment of women's inheritance rights in the patriarchal culture of the Batak Toba tribe in Unte Mungkur Village, North Tapanuli Regency, has not fulfilled the values of justice for women. Second, obstacles to fulfilling women's inheritance rights in the patriarchal culture of the Toba Batak tribe in Unte Mungkur Village are caused by patriarchal culture and the presence of habataon (for example Batak) burdens on women. Family law and inheritance can be developed towards a parental/bilateral legal system so that men and women are given equal status and several matters in customary regulations must be corrected to fulfill human rights and elements of justice for all regardless of gender.